In situ and satellite-based estimates of cloud properties and aerosol–cloud interactions over the southeast Atlantic Ocean - S. Gupta; S. Gupta; S. Gupta; G. M. McFarquhar; G. M. McFarquhar; J. R. O'Brien; J. R. O'Brien; M. R. Poellot; D. J. Delene; I. Chang; L. Gao; F. Xu; et al. (Atmospheric Chemistry and Physics, 2022)
In situ cloud probe data from the NASA ObseRvations of Aerosols above CLouds and their intEractionS (ORACLES) field campaign were used to estimate the effective radius (Re), cloud optical thickness (τ), and cloud droplet concentration (Nc) for marine stratocumulus over the southeast Atlantic Ocean. The in situ Re, τ, and Nc were compared with co-located Moderate Resolution Imaging Spectroradiometer (MODIS) retrievals of Re and τ and MODIS-derived Nc. For 145 cloud profiles, a MODIS retrieval was co-located with in situ data with a time gap of less than 1 h. On average, the MODIS Re and τ (11.3 µm and 11.7) were 1.6 µm and 2.3 higher than the in situ Re and τ with Pearson's correlation coefficients (R) of 0.77 and 0.73, respectively. The average MODIS Nc (151.5 cm−3) was within 1 cm−3 of the average in situ Nc with an R of 0.90.